Helicobacter pylori Infection Impairs Endothelial Function Through an Exosome‐Mediated Mechanism. Issue 6 (17th March 2020) - Xia, Xiujuan; Zhang, Linfang; Chi, Jingshu; Li, Huan; Liu, Xiaoming; Hu, Tingzi; Li, Rong; Guo, Yinjie; Zhang, Xue; Wang, Hui; Cai, Jin; Li, Yixi; et al.
Abstract : Background: Epidemiological studies have suggested an association between Helicobacter pylori ( H pylori ) infection and atherosclerosis through undefined mechanisms. Endothelial dysfunction is critical to the development of atherosclerosis and related cardiovascular diseases. The present study was designed to test the hypothesis that H pylori infection impaires endothelial function through exosome‐mediated mechanisms. Methods and Results: Young male and female patients (18‐35 years old) with and without H pylori infection were recruited to minimize the chance of potential risk factors for endothelial dysfunction for the study. Endothelium‐dependent flow‐mediated vasodilatation of the brachial artery was evaluated in the patients and control subjects. Mouse infection models with CagA + H pylori from a gastric ulcer patient were created to determine if H pylori infection‐induced endothelial dysfunction could be reproduced in animal models. H pylori infection significantly decreased endothelium‐dependent flow‐mediated vasodilatation in young patients and significantly attenuated acetylcholine‐induced endothelium‐dependent aortic relaxation without change in nitroglycerin‐induced endothelium‐independent vascular relaxation in mice. H pylori eradication significantly improved endothelium‐dependent vasodilation in both patients and mice with H pylori infection. Exosomes from conditioned media of human gastric epithelial cells cultured with CagA + H pylori or serum exosomes from patients and mice with H pylori infection significantly decreased endothelial functions with decreased migration, tube formation, and proliferation in vitro. Inhibition of exosome secretion with GW4869 effectively preserved endothelial function in mice with H pylori infection. Conclusions: H pylori infection impaired endothelial function in patients and mice through exosome‐medicated mechanisms. The findings indicated that H pylori infection might be a novel risk factor for cardiovascular diseases.